A method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration

CN122686985APending Publication Date: 2026-09-04XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611097389.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

现有技术主要沿两条技术路线开展优化,但各自存在三类无法兼顾的突出缺陷:

Benefits of technology

1、本方法通过工艺调控形成AlN晶界网络加TiC晶内弥散双模态构型,晶界处三维准连续AlN可强力钉扎晶界、抑制晶粒长大,大幅提升材料高温强度与抗蠕变性能,晶内均匀分布的纳米TiC依靠Orowan位错绕过机制阻碍位错运动,实现室温强韧化,两种强化机制协同作用,解决传统颗粒增强铝基复合材料“强度提升则塑韧性骤降”的固有矛盾,在提高材料硬度、比强度的同时保留良好延伸率与断裂韧性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122686985A_ABST
    Figure CN122686985A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal matrix composite material preparation, and discloses a preparation method of an intracrystalline dispersed TiC and grain boundary network AlN particle configuration reinforced aluminum matrix composite material, which comprises four steps: firstly, a core-shell powder is prepared by depositing an AlN precursor on the surface of aluminum powder; a core double-shell composite powder is obtained by modifying TiC electrostatic adsorption; a low-temperature pulse pre-pressing protective surface film is prepared; and a multi-stage pulse sintering is performed to induce local micro-melting of the matrix, and the composite material with intracrystalline dispersed TiC and grain boundary enriched AlN is obtained by relying on solid-liquid interface separation. The method forms an AlN grain boundary network and TiC intracrystalline dispersion double-mode configuration through process control, the three-dimensional quasi-continuous AlN at the grain boundary can strongly pin the grain boundary and inhibit the grain growth, and the high-temperature strength and creep resistance of the material are greatly improved, the uniformly distributed nanometer TiC in the crystal can hinder the dislocation movement by the Orowan dislocation bypass mechanism, the room temperature strength and toughness are improved, and the two kinds of strengthening mechanisms work together to meet the use needs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal matrix composite material preparation technology, specifically a method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration. Background Technology

[0002] Particle-reinforced aluminum matrix composites possess broad application prospects in aerospace and rail transportation due to their advantages of high specific strength, high specific modulus, wear resistance, and lightweight properties. However, traditional powder metallurgy preparation processes suffer from an inherent core contradiction: while increasing the amount of reinforcing particles can significantly improve material strength and hardness, it drastically reduces elongation and fracture toughness. This bottleneck stems from an inherent defect in the spatial distribution pattern of the reinforcing particles within the aluminum matrix. Existing technologies mainly focus on optimization along two technical routes, but each has three prominent drawbacks that cannot be simultaneously addressed: Defects of uniformly dispersed single-particle systems: Represented by in-situ self-generated nano-TiC aluminum-based composites, these systems rely on in-situ reactions during casting to achieve uniform distribution of nanoparticles throughout the entire distribution. While this can leverage the Orowan dislocation strengthening effect of nanoparticles, it cannot achieve differentiated particle configurations at grain boundaries and within grains. Secondary agglomeration of nanoparticles is prone to occur during the casting and solidification stage, and stress concentration sources are formed in local particle-rich areas, significantly weakening the material's plasticity. Relying solely on the global strengthening of a single type of particle, and lacking grain boundary pinning phases, the grains tend to coarsen during high-temperature service, resulting in a significant decrease in high-temperature strength.

[0003] Defects of single-particle grain boundary network configuration systems: Taking aluminum-based composite materials with micron-sized alumina forming a three-dimensional network along the powder boundary as an example, only micron-sized ceramic particles are enriched at the grain boundaries to form a continuous skeleton, which can inhibit grain growth and improve high-temperature performance to a certain extent. However, the interior of the grains is a pure aluminum matrix without reinforcing phases, and it is impossible to use nanoparticles to achieve intragranular dispersion strengthening, resulting in insufficient room temperature strengthening efficiency. Introducing only a single type of ceramic particle cannot simultaneously exert the two synergistic strengthening mechanisms of grain boundary pinning and intragranular dislocation blocking. Micron-sized grain boundary particles are prone to inducing interface debonding, and cracks propagate rapidly along the grain boundaries under stress, resulting in limited improvement in ductility and toughness.

[0004] Common shortcomings in the synergistic regulation of two-phase particles: Existing two-phase hybrid reinforcement schemes simply mix two types of ceramic particles through mechanical ball milling. The two types of particles are randomly and disorderly distributed in the matrix, and cannot actively achieve the partitioned configuration of "one type of particles being oriented and retained at the grain boundaries, and the other type of particles being dispersed and embedded in the grains". The single strengthening mechanism cannot complement each other. Either the grain boundary strengthening is insufficient and the grains are easy to coarsen, or the content of nanoparticles in the grains is too low and the dislocation strengthening effect is weak, making it difficult to simultaneously achieve a combination of high strength, high toughness and heat resistance. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing an aluminum matrix composite material with an intracrystalline dispersed TiC and grain boundary network AlN particle configuration, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing an aluminum matrix composite material reinforced with intragranular dispersed TiC and grain boundary network AlN particles, the specific steps of which are as follows: Step 1: Coating with aluminum nitride precursor Al-Mg-Si aluminum alloy powder was placed in a fluidized bed, and an amorphous aluminum nitride precursor film was deposited on the powder surface using atomic layer deposition / chemical vapor deposition at 80-200℃ to obtain core-shell structured composite powder A. Step 2: Electrostatic self-assembly and adsorption of nano-TiC Surface modification of nano-TiC particles was performed, and TiC was uniformly and monodispersedly adsorbed on the surface of composite powder A through electrostatic self-assembly in a liquid nonpolar medium to obtain core-double shell structured composite powder B. Step 3: Low-temperature pulse pre-densification After vacuum degassing and sealing of composite powder B, pulsed current and unidirectional pressure are applied at 300-500℃ to pre-compress the powder plastically and keep the aluminum nitride film continuous, thus completing the pre-densification of the preform. Step 4: Multi-stage pulsed discharge plasma sintering In a vacuum environment, the temperature is first raised to 520-580℃ and held at medium pressure. A short pulse current is then applied and the pressure is released to induce local micro-melting of the matrix. After holding at low pressure, high pressure is applied and the furnace is cooled. The dual-mode composite material with AlN-rich grain boundaries and TiC-dispersed within the grains is formed by the pushing effect of the solid-liquid interface.

[0007] Preferably, the aluminum alloy powder in step one is spherical powder of 200 mesh to 400 mesh, atomic layer deposition cycled 20 to 50 times, and the aluminum nitride precursor film thickness is 5 nm to 20 nm.

[0008] Preferably, the TiC particles in step two have an average particle size of 10 nm to 50 nm, are modified with a silane coupling agent or a cationic polyelectrolyte, and have a Zeta potential of > +30 mV or < -30 mV in the pH range of 6 to 8.

[0009] Preferably, in step three, the unidirectional pressure is 150MPa to 300MPa, the pulse current duty cycle is 20% to 50%, and the frequency is 10Hz to 100Hz, so that the pre-densification of the billet reaches 85% to 92% of the theoretical density.

[0010] Preferably, the sintering vacuum degree in step four is higher than 10. -3 Pa, first-stage sintering pressure 50MPa~100MPa, holding time 5~15min.

[0011] Preferably, in step four, the pulse peak value is increased to 3 to 5 times the initial value within 0.5 to 2 seconds, the pressure is simultaneously reduced to 0 to 5 MPa, the liquid phase volume fraction is controlled to be ≤15%, and after low-pressure heat preservation for 1 to 3 minutes, a secondary pressure cooling of 200 MPa to 350 MPa is applied.

[0012] Preferably, the determination criterion for the instantaneous local melting of the matrix in step four is that the resistance of the sintering mold first decreases instantaneously and then rises again, and AlN with a wetting angle greater than 90° and part of TiC are pushed to the grain boundary by the solid-liquid interface front to form a three-dimensional quasi-continuous network.

[0013] Preferably, in the cooling stage described in step four, the aluminum alloy is epitaxially grown with unmelted powder cores, and the TiC that is not retained at the grain boundaries is carried into the interior of the grains by the transient liquid phase.

[0014] Preferably, the volume fraction of aluminum nitride at the grain boundaries in the prepared composite material accounts for more than 80% of the total volume of aluminum nitride in the material.

[0015] Preferably, the volume fraction of TiC particles inside the grains in the prepared composite material accounts for 50% to 70% of the total TiC volume of the material.

[0016] The beneficial effects of this invention are as follows: 1. This method forms a dual-mode configuration of AlN grain boundary network plus TiC intragranular dispersion through process control. The three-dimensional quasi-continuous AlN at the grain boundary can strongly pin the grain boundary and inhibit grain growth, which greatly improves the high temperature strength and creep resistance of the material. The uniformly distributed nano-TiC in the grain relies on the Orowan dislocation bypass mechanism to hinder dislocation movement and achieve room temperature toughening. The two strengthening mechanisms work together to solve the inherent contradiction of "the strength increases but the toughness drops sharply" in traditional particle-reinforced aluminum matrix composites. While improving the material's hardness and specific strength, it retains good elongation and fracture toughness. 2. This method first constructs an AlN precursor shell through atomic layer deposition and achieves TiC monodisperse coating through electrostatic self-assembly, completing the layered pre-arrangement of the two-phase particles in advance during the powder stage; then, it relies on the solid-liquid pushing effect of the transient liquid phase during sintering to accurately separate the two-phase particles. Unlike the random agglomeration and local high-stress defects caused by traditional ball milling and powder mixing, this method can accurately control more than 80% of AlN to be enriched at grain boundaries and 50%~70% of TiC to remain in the grains, greatly reducing the crack initiation induced by particle agglomeration and improving the overall mechanical uniformity and fatigue performance of the material. 3. This method relies on standardized processes such as fluidized bed coating, electrostatic self-assembly, and multi-stage pulsed discharge plasma sintering. The temperature, pressure, and current parameters at each stage are clearly adjustable, and the configuration can be accurately replicated. It does not require complex in-situ melting and casting reactions, avoiding the problem of secondary agglomeration of particles during melt solidification. The resulting composite material has multiple advantages such as high strength and toughness at room temperature, resistance to grain coarsening at high temperature, and wear resistance. It is suitable for long-term service conditions of lightweight structural components in aerospace and rail transportation. Compared with aluminum matrix composites with single uniform particles and single grain boundary network configuration, the comprehensive application performance is significantly improved. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the XRD phase diffraction structure of the composite material of the present invention; Figure 2 This is a schematic diagram of the elemental surface scan distribution structure of the composite material of the present invention; Figure 3 This is a schematic diagram of the SEM microstructure and potential energy dispersive spectroscopy sampling structure of the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] like Figures 1 to 3 As shown, this embodiment of the invention provides a method for preparing an aluminum matrix composite material reinforced with intragranular dispersed TiC and grain boundary network AlN particles. The specific steps are as follows: Step 1: Coating with aluminum nitride precursor Al-Mg-Si aluminum alloy powder was placed in a fluidized bed, and an amorphous aluminum nitride precursor film was deposited on the powder surface using atomic layer deposition / chemical vapor deposition at 80-200℃ to obtain core-shell structured composite powder A. Step 2: Electrostatic self-assembly and adsorption of nano-TiC Surface modification of nano-TiC particles was performed, and TiC was uniformly and monodispersedly adsorbed on the surface of composite powder A through electrostatic self-assembly in a liquid nonpolar medium to obtain core-double shell structured composite powder B. Step 3: Low-temperature pulse pre-densification After vacuum degassing and sealing of composite powder B, pulsed current and unidirectional pressure are applied at 300-500℃ to pre-compress the powder plastically and keep the aluminum nitride film continuous, thus completing the pre-densification of the preform. Step 4: Multi-stage pulsed discharge plasma sintering In a vacuum environment, the temperature is first raised to 520-580℃ and held at medium pressure. A short pulse current is then applied and the pressure is released to induce local micro-melting of the matrix. After holding at low pressure, high pressure is applied and the furnace is cooled. The dual-mode composite material with AlN-rich grain boundaries and TiC-dispersed within the grains is formed by the pushing effect of the solid-liquid interface.

[0020] By pre-arranging the two-phase reinforcing particles in layers during the powder stage, the drawbacks of the random and disordered distribution of traditional mixed powder particles are overcome. With the help of the solid-liquid interface sorting effect generated by the instantaneous liquid phase during sintering, the spatial partitioning of the two ceramic particles is precisely achieved. The grain boundary AlN network can pin the grain boundaries to inhibit grain coarsening, while the intragranular TiC achieves dispersion strengthening through the dislocation bypass mechanism. The two strengthening mechanisms work together to effectively solve the problem of simultaneously improving the strength and toughness of aluminum-based composite materials. The overall process is seamless, the adjustable range of process parameters is clear, and the configuration reproducibility is good. The final product has better uniformity of microstructure and is suitable for the use of lightweight structural components in aerospace and rail transportation.

[0021] In step one, the aluminum alloy powder is spherical powder of 200-400 mesh, and the atomic layer deposition cycle is 20-50 times, with the aluminum nitride precursor film thickness being 5nm-20nm.

[0022] Using spherical powder with the corresponding mesh size provides better flowability, ensuring uniform and intact coating film. Matching fluidized bed deposition conditions and precisely controlling film thickness and cycle number can prevent the shell from breaking due to being too thin or agglomerating due to being too thick.

[0023] In step two, the average particle size of TiC particles is 10nm to 50nm, and they are modified with silane coupling agents or cationic polyelectrolytes. The zeta potential in the pH range of 6 to 8 is > +30mV or < -30mV.

[0024] This particle size of nano-TiC has excellent dispersion enhancement effect. Modified and controlled potential can ensure sufficient stability of electrostatic adsorption, prevent TiC from agglomerating, and achieve uniform coating and adhesion of single particles on the outer surface of precursor powder.

[0025] In step three, the unidirectional pressure is 150MPa to 300MPa, the pulse current duty cycle is 20% to 50%, and the frequency is 10Hz to 100Hz. After pre-densification, the density of the billet reaches 85% to 92% of the theoretical density.

[0026] Matching temperature, pressure, and pulse parameters can achieve full plastic filling of powder while protecting the AlN precursor shell from cracking. The preset density range can balance the subsequent sintering degassing efficiency and the stability of the green body forming.

[0027] In step four, the sintering vacuum degree is higher than 10. -3 Pa, first-stage sintering pressure 50MPa~100MPa, holding time 5~15min.

[0028] The high vacuum environment can avoid sintering oxidation pollution. The first-stage sintering parameters can achieve initial bonding of the powder interface, laying a uniform and dense microstructure foundation for subsequent instantaneous liquid phase control of particle arrangement.

[0029] In step four, the pulse peak value is increased to 3 to 5 times the initial value within 0.5 to 2 seconds, and the pressure is simultaneously reduced to 0 to 5 MPa. The liquid phase volume fraction is controlled to be ≤15%. After low-pressure heat preservation for 1 to 3 minutes, a secondary pressure cooling of 200 MPa to 350 MPa is applied.

[0030] Short-duration pulse mutations can precisely and controllably trigger local micro-liquid phases, limiting excessively high liquid phase ratios to prevent abnormal grain growth. Segmented pressure settings balance particle sorting effects with the final overall density of the material.

[0031] In step four, the determination of instantaneous local melting of the matrix is ​​based on the sintering mold resistance first decreasing instantaneously and then increasing again, and AlN with a wetting angle greater than 90° and some TiC being pushed to the grain boundary by the solid-liquid interface front to form a three-dimensional quasi-continuous network.

[0032] The change in mold resistance can intuitively and conveniently determine whether local melting has occurred. It can spontaneously separate two-phase particles based on the difference in wetting characteristics, and can construct a continuous grain boundary strengthening network in situ without the need for additional additives.

[0033] In step four, during the cooling stage, the aluminum alloy grows epitaxially with unmelted powder cores, and TiC that is not retained at the grain boundaries is carried into the interior of the grains by the transient liquid phase.

[0034] By relying on the original powder core for directional crystallization growth, internal porosity defects can be reduced, and the liquid phase encapsulation effect naturally distributes the remaining TiC particles, stably forming the preset intracrystalline dispersion-strengthened microstructure.

[0035] In the composite material, the volume fraction of aluminum nitride at the grain boundaries accounts for more than 80% of the total volume of aluminum nitride in the material.

[0036] This ratio ensures the integrity of the continuous AlN network at grain boundaries, fully leverages the grain boundary pinning effect, suppresses grain growth under high-temperature conditions, and improves the high-temperature strength and creep resistance of the material.

[0037] In the prepared composite material, the volume fraction of TiC particles inside the grains accounts for 50% to 70% of the total TiC volume of the material.

[0038] This ratio range can fully utilize the dislocation strengthening effect of nano-TiC without causing local aggregation due to excessive intracrystalline particles, thus balancing the increase in material strength and plastic deformation capacity.

[0039] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an aluminum matrix composite material reinforced with intragranular dispersed TiC and grain boundary network AlN particles, characterized in that, The specific steps are as follows: Step 1: Coating with aluminum nitride precursor Al-Mg-Si aluminum alloy powder was placed in a fluidized bed, and an amorphous aluminum nitride precursor film was deposited on the powder surface using atomic layer deposition / chemical vapor deposition at 80-200℃ to obtain core-shell structured composite powder A. Step 2: Electrostatic self-assembly and adsorption of nano-TiC Surface modification of nano-TiC particles was performed, and TiC was uniformly and monodispersedly adsorbed on the surface of composite powder A through electrostatic self-assembly in a liquid nonpolar medium to obtain core-double shell structured composite powder B. Step 3: Low-temperature pulse pre-densification After vacuum degassing and sealing of composite powder B, pulsed current and unidirectional pressure are applied at 300-500℃ to pre-compress the powder plastically and keep the aluminum nitride film continuous, thus completing the pre-densification of the preform. Step 4: Multi-stage pulsed discharge plasma sintering In a vacuum environment, the temperature is first raised to 520-580℃ and held at medium pressure. A short pulse current is then applied and the pressure is released to induce local micro-melting of the matrix. After holding at low pressure, high pressure is applied and the furnace is cooled. The dual-mode composite material with AlN-rich grain boundaries and TiC-dispersed within the grains is formed by the pushing effect of the solid-liquid interface.

2. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: The aluminum alloy powder mentioned in step one is spherical powder of 200-400 mesh, and atomic layer deposition is performed 20-50 times, with the aluminum nitride precursor film thickness being 5nm-20nm.

3. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: The TiC particles mentioned in step two have an average particle size of 10nm to 50nm, are modified with silane coupling agents or cationic polyelectrolytes, and have a Zeta potential of > +30mV or < -30mV in the pH range of 6 to 8.

4. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: In step three, the unidirectional pressure is 150MPa to 300MPa, the pulse current duty cycle is 20% to 50%, and the frequency is 10Hz to 100Hz. After pre-densification, the density of the billet reaches 85% to 92% of the theoretical density.

5. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: The sintering vacuum degree mentioned in step four is higher than 10. -3 Pa, first-stage sintering pressure 50MPa~100MPa, holding time 5~15min.

6. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: In step four, the pulse peak value is increased to 3 to 5 times the initial value within 0.5 to 2 seconds, and the pressure is simultaneously reduced to 0 to 5 MPa. The liquid phase volume fraction is controlled to be ≤15%. After low-pressure heat preservation for 1 to 3 minutes, a secondary pressure of 200 MPa to 350 MPa is applied for cooling.

7. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: The determination criterion for instantaneous local melting of the matrix in step four is that the resistance of the sintering mold first drops instantaneously and then rises again, and AlN with a wetting angle greater than 90° and some TiC are pushed to the grain boundary by the solid-liquid interface front to form a three-dimensional quasi-continuous network.

8. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: In step four, during the cooling stage, the aluminum alloy grows epitaxially from an unmelted powder core, and the TiC that is not retained at the grain boundaries is carried into the interior of the grain by the transient liquid phase.

9. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: In the prepared composite material, the volume fraction of aluminum nitride at the grain boundaries accounts for more than 80% of the total volume of aluminum nitride in the material.

10. The method for preparing an aluminum matrix composite material with intragranular dispersed TiC and grain boundary network AlN particle configuration according to claim 1, characterized in that: In the prepared composite material, the volume fraction of TiC particles inside the grains accounts for 50% to 70% of the total TiC volume of the material.